A Long-Term Follow-Up Programme for Maintenance of Motor Function after Stroke: Protocol of the life after Stroke—The LAST Study. (22nd November 2012) - Askim, Torunn; Langhammer, Birgitta; Ihle-Hansen, Hege; Magnussen, Jon; Engstad, Torgeir; Indredavik, Bent
Abstract : Background . There are no evidence-based strategies that have been shown to be superior in maintaining motor function for months to years after the stroke. The LAST study therefore intends to assess the effect of a long-term follow-up program for stroke patients compared to standard care on function, disability and health. Design . This is a prospective, multi-site randomised controlled trial, with blinded assessment 18 months after inclusion. A total of 390 patients will be recruited and randomised to a control group, receiving usual care, or to an intervention group 10 to 16 weeks after onset of stroke. Patients will be stratified according to stroke severity, age above 80, and recruitment site. The intervention group will receive monthly coaching on physical activity by a physiotherapist for 18 consecutive months after inclusion. Outcomes . The primary outcome is motor function (Motor Assessment Scale) 18 months after inclusion. Secondary outcomes are: dependency, balance, endurance, health-related quality of life, fatigue, anxiety and depression, cognitive function, burden on caregivers, and health costs. Adverse events and compliance to the intervention will be registered consecutively during follow-up.